Pengaruh Ketidakpuasan Karir terhadap Job Crafting dengan Dukungan Sosial dan Self Efficacy sebagai Variabel Moderator - Stepanus Gabriel Wibisono (Jurnal Indonesia Sosial Teknologi, 2022)
This research is motivated by individuals who do not always get satisfaction during their careers. The aims of this study were to find out how career dissatisfaction affects craft work and to test social support and self-efficacy moderated this relationship. This type of research is quantitative, the questionnaire is used as a data collection tool. Data were collected from a sample of 30 Romokalisari Toll Gate employees and processed using SPSS 25 software. Hypothesis testing showed that career dissatisfaction did not have a positive effect on job crafting, so social support and self-efficacy could increase the R Square value of the effect of career dissatisfaction on job crafting. Companies must maintain the level of career satisfaction of their employees and as much as possible to create a good and supportive work environment so that they feel motivated to create job crafting.